Design of two-component molecular crystals with defined melting points. Issue 8 (10th February 2023) - Perlovich, German L.
Abstract : The approach proposed in this study disclosed opportunities to predict whether it is possible to obtain co-crystals/salts with melting temperatures above/below the melting temperatures of the individual components. Abstract : The approach proposed in this study disclosed opportunities to predict whether it is possible to obtain co-crystals/salts (by selecting the second component) with melting temperatures above/below the melting temperatures of the individual components within two-component molecular crystals based on a preselected component (CF1).